The Characteristics of Biscuit Quality with Coffee (Coffea Arabica L.) Silver Skin Flour Substitution - Inawaty Sidabalok; Juni Hasrat Harefa; Asnurita Asnurita; Yonny Arita Tahir; Afrida Afrida (The University of Lampung, 2023)
Coffee silver skin flour can be effortlessly converted into various items, and its nutritional quality remains constant. Thus, exploring novel methods of utilizing it could result in sustainable and innovative products with consistent nutritional advantages. This study investigated the impact of using coffee silver skin flour on the quality of biscuits. This study used a completely randomized design (CRD) consisting of 5 levels of treatment and three replications. The percentages of wheat flour substituted with coffee silver skin flour were 0, 20, 40, 60, and 80%. Observation data were analyzed using ANOVA with F test and continued with Duncan's New Multiple Range Test (DNMRT) test at 1% significance level. The result showed that substituting wheat flour with coffee silver skin flour considerably altered the flour's moisture, ash, protein, and fat content. With increasing amounts of coffee silver skin flour, the moisture and ash contents increased, while the protein and fat contents decreased. Biscuits that were most favored by panelists were in treatment A (100% wheat flour with 0% coffee silver skin flour) with moisture, ash, protein, and fat content of 1.31, 0.25, 18.50, and 19.45%, respectively. Biscuits made from coffee silver skin flour meet the quality requirements set by SNI 2973:2011, except for treatment E (0% wheat flour with 100% coffee silver skin flour), as the moisture content exceeds the specified criteria. Keywords: Biscuit quality, Characteristics, Coffee silver skin